Pemikiran Tun Dr. Mahathir bin Mohamad - Abdul Mua'ti. (Kuala Lumpur: Penerbit Universiti Malaya, 2007)
Analysis of Mahathir Mohamad's speeches on political, economic, sociocultural, and international issues in Malaysia delivered to UMNO's General Assembly from 1982 up to 2003.
Revision of the author's thesis (Ph. D.)--Universiti Malaya.
Includes bibliographical references (p. 365-371) and index.
Keywords: Mahathir bin Mohamad, -- 1925-; Malaysia -- -- Politics and government